A survey based study of public perception towards cell phone use and its association with health complications in an urban setting of Dhaka City (Asian Journal of Medical and Biological Research, 2017)
With the advancement of science and technology, the worldwide market of cell phone is growing rapidly and the average lifespan of these equipment is shortening. These electronic equipment, containing toxic elements, imposes high risks leading to health complications. This survey based study is an endeavor to observe public awareness towards cell phone use and its correlation to health complications such as hearing impairment, back pain, problems in eye, headache etc. Remarkably this pilot study implies that adverse health effects for using cell phones are greater in male than in female which can be a great concern for our public health.Asian J. Med. Biol. Res. December 2016, 2(4): 518-522